(untitled) (Fiep Bulletin - online, 2012)
The SPECIAL THEME FIEP BULLETIN about HUMAN KINETICS starts up a new concept of theme publishings to be organized by the FÉDERATION INTERNATIONALE D’EDUCATION PHYSIQUE – FIEP, with the aim of contributing to the diffusion of the scientific knowledge developed in Physical Education, in the countries where it is present. This first SPECIAL THEME FIEP BULLETIN talks about the Human Kinetics Science and its different applications, and was organized by Prof. Dr. João Batista Andreotti Gomes Tojal, PhD in Human Kinetics by the Technical University of Lisbon, and Vice- President of the Brazilian Federal Physical Education Council - CONFEF.